2010
DOI: 10.19030/rbis.v14i2.495
|View full text |Cite
|
Sign up to set email alerts
|

The Process Of Creating XBRL Instance Documents: A Research Framework

Abstract: The past decade has witnessed a technological revolution fueled by the widespread use of the Internet, web technologies, and their applications. Within financial reporting, proponents of extensible Business Reporting Language (XBRL) argue that XBRL will revolutionize financial reporting since it allows corporate financial information to be aggregated, transmitted, and analyzed quicker and more accurately (Hoffman and Strand 2001;Hannon 2002;Bovee et al. 2005;Willis 2005;Cox 2006). The SEC recently mandated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Problems of disclosure overload for individual users include the time associated with searching and locating relevant information (Janvrin and Mascha, 2010). Paredes (2003) gives a broad overview of the effect of information overload and implications for mandatory disclosure requirements, reviewing empirical evidence from investor psychology and behavioural finance fields.…”
Section: Areas For Improvement In Disclosurementioning
confidence: 99%
“…Problems of disclosure overload for individual users include the time associated with searching and locating relevant information (Janvrin and Mascha, 2010). Paredes (2003) gives a broad overview of the effect of information overload and implications for mandatory disclosure requirements, reviewing empirical evidence from investor psychology and behavioural finance fields.…”
Section: Areas For Improvement In Disclosurementioning
confidence: 99%
“…Prior research in the XBRL literature has primarily focused on the theoretical attributes and benefits associated with XBRL-based reporting from a user perspective (Alles & Piechocki, 2012;Baldwin, Brown & Trinkle, 2006;Janvrin & Mascha, 2010;Vasarhelyi, Chan & Krahel, 2012;Muthusamy, Bir & Birt, 2017). Recent research has found that the anticipated benefits of XBRL focus predominantly on efficiency within the realm of the data and report-producers and on effectiveness within the realm of the data and report-consumers (Robb, et al 2016).…”
Section: Organizational Use Of Ismentioning
confidence: 99%
“…Many studies reveal positive association between the quality of disclosures and forecast accuracy (Hope, 2003). Many expect XBRL to reduce re-keying information, diminish errors in duplicated data entry, and thus increase data accuracy ( Janvrin and Mascha, 2010;Pinsker and Wheeler, 2009). Yoon et al (2011) find XBRL to reduce information asymmetry.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%